Agricola's Ukko in the light of archaeology: a chronological and interpretative study of ancient Finnish religion - Salo, Unto (Scripta Instituti Donneriani Aboensis, 1990)
No written sources of ancient Finnish religion have been preserved from the pre-Christian period. Study of the subject is thus based on later historical data, folk poetry and other recorded national traditions, supplemented by etymology and onomastics. A valuable basis for study is provided by the verses of Mikael Agricola in the preface to his Psalms of David from 1551. Here Agricola lists the gods of Karelia and Häme. He admittedly subjects them to Christian censure, but he is also in these verses the first systematizer and the first theologian of our ancient religion. He created twin Olympuses of the old religion, two anthropomorphic god-worlds, the sub-structure of which includes the worship of spirits, animals and the dead. From the point of view of archaeology, Agricola's Ukko, 'old man', is one of the most interesting figures in ancient religion. According to Agricola, Ukko was (only) a Karelian god, but scholars have long considered that he was referring to the universally feared Ukko, Ukkonen, the god of thunder, who would have fitted equally well among the gods of Häme (Tavastland).